Desarrollo de una aplicación móvil con realidad aumentada usando la herramienta metaio aplicada al turismo en el Cantón Chambo - Ramos Santarrosa, Daniela Briggete (2022)
The research is carried out in the tourist field of Chambo, this being a very important activity due to the large number of potentially tourist places, but which significantly lack available and timely information for tourists, however having a problem but at the same time an opportunity to propose innovative solutions and find a way to improve the management of tourist information in the canton, making it more interactive and interesting, timely and relevant. It is in this scenario where augmented reality technology and mobile applications help boost the tourism sector. The objective of this project is oriented to the development of a mobile application with augmented reality, using the metaio sdk tool applied to tourism in the Chambo canton. The development of the application was carried out through the application of the Iconix methodology and finally the usability of the system was evaluated through the Nielsen heuristic method, surveys were applied to experienced users in usability, it is concluded that 80% of the users recommend using the system